The Fight Against Malaria: A New Index for Quantifying and Assessing Policy Implementation Actions to Reduce Malaria Burden in Sub-Saharan Africa. - Bethencourt, Carlos; Marrero, Gustavo A.; Ngoudji, Charlie Y. (Journal of Development Studies, 2023)
We aggregate information from the World Malaria Reports on 61 different antimalarial policies to develop an extensive synthetic index (MaPI) for 44 SSA countries between 1990 and 2017. We observe an increase of convergence in polices' implementation in the region, starting in more developed countries and reaching less developed countries from the mid-2000s. Using a difference-in-difference events study design, we find that prevention, diagnosis and treatment are key policies to reduce malaria mortality and prevalence: an increase of about 10 p.p. of these policies generates a mortality cumulative decrease of around 8 p.p. and a prevalence cumulative decrease of 13 p.p. after five years. We also use available data on policy coverage for a reduced subset of policies to construct an intensive margin version of the index. Main results are consistent to the ones derived from the extensive version. Finally, we prove the robustness of our results with a large battery of checks related to model specifications, econometric techniques, data sources and falsification tests.